2020
DOI: 10.1002/eqe.3243
|View full text |Cite
|
Sign up to set email alerts
|

Centrifuge modelling of structures with oil dampers under seismic loading

Abstract: Summary Experimental research into the seismic performance of buildings with passive oil dampers has so far been restricted to large‐scale testing of frames erected on laboratory shaking tables that ignore the foundation soil below. This simplification of the problem falls short of replicating dynamic soil‐structure interaction that would occur in the field. This paper presents the first experimental attempt at utilising high gravity dynamic centrifuge testing to replicate the response of a damped building at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Note, however, it is possible to achieve the identity cps=β2cts for the FVDs with a change in damping fluid. This is a practical change but it does require that the damping fluid has an appropriate viscosity 54,55 . Both these options are explored here.…”
Section: Seismic Performance Of a Steel Building Equipped With Nonlin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Note, however, it is possible to achieve the identity cps=β2cts for the FVDs with a change in damping fluid. This is a practical change but it does require that the damping fluid has an appropriate viscosity 54,55 . Both these options are explored here.…”
Section: Seismic Performance Of a Steel Building Equipped With Nonlin...mentioning
confidence: 99%
“…This is a practical change but it does require that the damping fluid has an appropriate viscosity. 54,55 Both these options are explored here.…”
Section: Total Number Of Elementsmentioning
confidence: 99%
“…Huergo et al [4] also showed that soil flexibility could decrease the equivalent damping ratio of FVDs, and increase the displacement of tall buildings on soft soils. More recently, experimental research by Boksmati et al [5] found that SSI can reduce the energy dissipated by the dampers. De Domenico et al [6] investigated the effect of soft soil conditions on the seismic performance of Tuned Inter Dampers (TID) by modeling the seismic accelerograms as a filtered Gaussian random process.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that significant damping is afforded by the foundation soil that can be beneficial in reducing the earthquake-induced vibrations in portal frame structures. More recently Boksmati and Madabhushi [6] studied model structures fitted with viscous dampers and tracked the energy dissipation in the viscous dampers as well as in the foundation soil. They concluded that dynamic soil-structure interaction and consequent damping in the foundation soil can benefit the overall structural performance during a seismic event.…”
Section: Introductionmentioning
confidence: 99%